2022
DOI: 10.3390/ani12010118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oregano Oil and Cobalt Lactate on Sheep In Vitro Digestibility, Fermentation Characteristics and Rumen Microbial Community

Abstract: The objective of this experiment was to evaluate the effect of different EOC (0.1425% cobalt lactate + 1.13% oregano essential oil + 98.7275% carrier) levels on in vitro rumen fermentation and microbial changes. Six EOC levels (treatments: 0 mg·L−1, CON; 50 mg·L−1, EOC1; 100 mg·L−1, EOC2; 400 mg·L−1, EOC3; 800 mg·L−1, EOC4 and 1500 mg·L−1, EOC5) were selected to be used to in vitro incubation. The in vitro dry matter digestibility (IVDMD), in vitro neutral detergent fiber digestibility (IVNDFD), in vitro acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
1
17
1
Order By: Relevance
“…Although no significant differences were observed, adding 0.02 and 0.04% OEO reduced ruminal NH 3 -N concentration by 16 and 22%, respectively. These results can be attributed to the antimicrobial activity of OEO [44] by inhibiting ammonia-producing bacteria [45], produced by thymol, one of the main components of OEO (Lippia graveolens) [46], acting on rumen microorganisms and by affecting protein deamination [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no significant differences were observed, adding 0.02 and 0.04% OEO reduced ruminal NH 3 -N concentration by 16 and 22%, respectively. These results can be attributed to the antimicrobial activity of OEO [44] by inhibiting ammonia-producing bacteria [45], produced by thymol, one of the main components of OEO (Lippia graveolens) [46], acting on rumen microorganisms and by affecting protein deamination [47].…”
Section: Discussionmentioning
confidence: 99%
“…VFAs are the main products of carbohydrate degradation in diets and provide most of the energy precursors for metabolic processes in ruminants, so a variation in the acetate: propionate ratio could affect the productive performance [45,48]. Other studies have reported that the inclusion of different levels of OEO has not affected VFA production [41,49] or the acetate: propionate ratio [13].…”
Section: Discussionmentioning
confidence: 99%
“…For the genus level, Uncultured_bacterium_f_Muribaculaceae was the most common genus, found in the rumen microbial community of sheep as well [ 24 ], being slightly more predominant on day 14 post ivermectin usage in this study. This bacterial genus could produce succinic acid as an important gluconeogenic intermediate and was helpful with polysaccharides degradation and metabolism [ 25 ].…”
Section: Discussionmentioning
confidence: 81%
“…Gas production is an important indicator reflecting the degree of rumen fermentation. The stronger the fermentation of the diet, the higher the microbial activity [ 36 , 37 ]. Previous studies have shown that the addition of rumen-protected methionine to the diet could significantly increase gas production [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%